Looking More Carefully: A Successful Bioblitz Orientation Activity at an Urban Public University. (21st January 2022) - Rokop, Megan; Srikanth, Rajini; Albert, Marc; Radonic, Catherine; Vincent, Rachel; Stevenson, Robert
A college freshman orientation activity incorporating citizen science was designed and implemented by a partnership between the University of Massachusetts Boston and the National Park Service. The goals of this study were to create an engaging citizen science experience for first-year college students who did not have prior background in the field, and to iterate and improve the activity (three consecutive summers, 2017–2019) so as to generate insights that may improve future citizen science projects. Over three years, students (468 total) largely unfamiliar with citizen science (92.6%) or iNaturalist (97.9% first-time users) employed the iNaturalist app to document the biodiversity of Thompson Island in Boston Harbor. Student outcomes were assessed using pre- and post-surveys, and survey data indicated that the bioblitz effectively engaged these students: More than 60% of students found the activity very or extremely engaging, and less than 1% found it not engaging. More than 70% of the students indicated they were somewhat, very, or extremely interested in learning about or participating in citizen science, and in returning to the Boston Harbor Islands, in the future. A similar percent also believed their data were somewhat, very, or extremely important to the islands and to the National Park Service. The students' self-reported level of engagement and interest shows how a fruitful campus-community collaboration can excite students from across majors in a citizen science project. The three iterations of this activity allowed us to make changes over time and gain insights that may be helpful to the design of future citizen science projects.